Emilio Pradilla Cobos. Capital, estado y vivienda en América Latina. México, D.F. : Fontamara, 1987. 308 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1987)
EMILIO PRADILLA COBOS. Capital, Estado y Vivienda en América Latina, Fontamara 27, México, D.F., 1987.